Community pharmacists’ views and experiences toward over-the-counter medicines misuse and abuse in Saudi Arabia: A qualitative study - Algarni, Mohammad; Jalal, Zahraa; Hadi, Muhammad Abdul; Alghamdi, Saleh (Frontiers in Pharmacology, 2022)
Abstract Background Community pharmacists are uniquely positioned to identify and address the issue of misuse and abuse of over-the-counter (OTC) medicines. To date, no study has explored the Saudi community pharmacists' views and experiences regarding aspects of OTC medicines misuse and abuse. Objective To explore the views and experiences of the Saudi community pharmacists towards OTC medicines misuse and abuse. Furthermore, we aimed to identify frequently misused and abused medicines, reasons and contributing factors, the role of pharmacists and potential risk-mitigating strategies. Methods Semi-structured interviews were conducted with a convenient sample of sixteen community pharmacists recruited from community pharmacies across the AL-Baha region, Saudi Arabia. Interviews were conducted using a pilot-tested interview guide in Arabic language. All interviews were audio-recorded, transcribed verbatim, translated from Arabic into English, and then thematically analysed. Results Analysis of interviews generated five main themes. Sedative antihistamines, cough products containing dextromethorphan, codeine-based analgesics, and non-codeine-based analgesics were commonly misused and abused OTC medicines. Managing ongoing medical conditions was the main reason for misusing OTC analgesics while recreational use and inducing sleep were the common reasons for abuse. Several factors contributing to misuse and abuse were reported, including unprofessional advice sought from other people, lack of awareness about medicines and commercial advertisement of OTC products. Community pharmacists identified misuse and abuse among customers by judging their behaviours and attitudes and using structured questioning techniques. Counselling customers on the appropriate use of medicines, providing safe alternatives and refusing to sell products were among commonly used actions of pharmacists to address misuse/abuse. Pharmacists proposed several strategies to reduce the risk of OTC medicines misuse/abuse, but believed that rescheduling OTC medicines with abuse potential to prescrioption-only medicine was the best option. Conclusion Community pharmacists believed that the misuse and abuse of OTC medicines amongst pharmacy customers was common. A multidimensional strategy consisting of upskilling community pharmacists, comprehensive review of OTC medicines sale regulations, and patient education to limit the risks of OTC medicines misuse/ abuse is required.